Endoscopic Multipoint Laser System for Objective Pediatric Airway Assessment. (20th October 2020) - Hall, Andrew Christopher; Navaratnam, Annakan Victor; Maughan, Elizabeth; Hartley, Benjamin; Hewitt, Richard J.; Butler, Colin
Abstract : Recent technological advances within aeronautical engineering have demonstrated the delivery of objective quantitative endoscopic measurements to within one‐hundredth of a millimeter. We sought to validate this emerging laser technology in a simulation‐based assessment of pediatric airway stenosis. A 4.4‐mm flexible endoscope, incorporating a laser measurement system projecting 49 laser points into the endoscopic view, was used to assess a simulated model of subglottic stenosis. Multiple anteroposterior and lateral measurements were obtained for each stenosis and compared with standard airway assessment techniques. Intra‐ and interobserver reliability was assessed. A total of 240 multipoint laser measurements were obtained of simulated airway stenosis. The mean difference from manual measurement was 0.1886 mm. The Bland‐Altman plot showed low bias (0.011) and narrow 95% limits of agreement (−0.46 to 0.48). This advanced endoscopic measurement technique shows great promise for clinical development to benefit ongoing assessment and treatment of evolving pediatric airway stenosis.